ANALISIS WILLINGNES TO PAY PETANI TERHADAP PUPUK ORGANIK BERSUBSIDI (Studi Kasus di Kabupaten Bantul dan Kota Yogyakarta, 2010) - , Tiwi Setyawati, SE., Dr. Poppy Ismalina, M.Ec.Dev. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to estimate the WTP values of society to the use of organic fertilizers, to analyze the characteristics of the people who exploit and use organic fertilizer subsidy, to analyze the factors that influence the willingness of the community in paying / buying subsidized organic fertilizers for agricultural land. The data used are household farmers who serve as the sample, where farmers are used as samples in this study are at the research sites in Bantul district and Yogyakarta City. The selection of two research sites was based on the pre survey conducted earlier research, which covers four areas in Yogyakarta Special Region which includes Bantul Regency, Regency Wates, Kulon Progo regency and municipality of Yogyakarta. This study analyzed data obtained qualitatively and quantitatively. The quantitative data obtained was used to determine the WTP model subsidized public using organic fertilizer using logit models with Microsoft Excel and Eviews 4.0. While the qualitative data processed descriptively used to determine the general condition of the public using subsidized organic fertilizers in the district of Bantul and Yogyakarta. The methods used to obtain qualitative and quantitative data is by interview and questionnaire presentation. Judging from the willingness to pay organic fertilizer Respondents in Bantul district nearly 47.57 percent was able to buy organic fertilizer according to the HET while only 21.67 percent of Yogyakarta City are able to buy organic fertilizer according to HET. While willingness to pay was good organic fertilizer respondents in Bantul district and Yogyakarta City are willing to pay for organic fertilizer with a price of Rp 700, -/kg. For the city of Yogyakarta approximately 66.67% of the 60 respondents were willing to pay for organic fertilizer with a price of Rp 700, - while the Bantul district of about 46.60 already able to afford organic fertilizer appropriately priced HET. Determinants of willingness to pay farmers to subsidized organic fertilizers proved not to be influenced by farmers' income, agricultural land owned, education ever undertaken by the farmer, age, number of workers who participate in farming families, the benefits of organic fertilizer, the number of livestock owned, agricultural areas, spesific price of fertilizer with the highest retail price, type of farmers (as owners or as workers), knowledge of organic fertilizer, and the existence of stalls selling organic fertilizer. While the factors that proved significant direct effect on willingness to pay farmers to subsidized organic fertilizers that farmers' education level, age, number of workers who participate in farming families, the highest retail price, and the existence of the kiosk.